The Understanding of Higher-Order Thinking Skills (HOTS) Among Middle School Science Teachers in Lhokseumawe, Indonesia - Riza; Safriana Safriana; Imam Wahyudi Winata; Indah Ameliah (LPPM Universitas Malikussaleh, 2024)
This study aims to evaluate the understanding of Higher-Order Thinking Skills (HOTS) among middle school science teachers in public schools in Lhokseumawe. Employing a quantitative descriptive design, data were collected from 15 teachers selected through purposive sampling. A 15-item multiple-choice test was administered, with each question targeting specific HOTS indicators, such as Bloom’s Taxonomy, project-based assessment, and analytical skills. The results revealed that while teachers demonstrated strong foundational knowledge of HOTS, with 93% showing proficiency in basic concepts and 87% understanding Bloom’s Taxonomy, significant gaps were observed in the practical application of HOTS. Only 60% of teachers showed proficiency in project-based assessment, and just 53% demonstrated strong analytical skills. Furthermore, while 73% of teachers recognized the importance of HOTS in education, only 60% understood its long-term benefits for student growth. These findings highlight the need for targeted professional development, resource provision, and mentorship programs to enhance teachers' ability to implement HOTS effectively in their teaching practices. Addressing these gaps will better equip educators to foster critical thinking and problem-solving skills among students.